SHOPEE MARKET SHARE CENTRALIZATION AND CHANGES IN INDONESIAN E-COMMERCE MARKET STRUCTURE - S. Reza Wildan; Yudha Saputra; Dicky Setiawan; Fadila Ulfah; Ahmad Soleh; Defika Putri Nastiti (Institut Agama Islam K.H. Sufyan Tsauri, 2026)
This study aims to analyze the centralization of market share on Shopee and its implications for changes in the Indonesian e-commerce market structure. The method used is qualitative research with a descriptive-analytical approach and case studies. Data were obtained through literature review and documentation in the form of industry reports, scientific journals, and publications related to the development of e-commerce in Indonesia. The analysis was conducted using the Structure Conduct Performance theoretical framework. The results show an increase in market concentration, characterized by Shopee's dominance in terms of visits and transaction activity compared to its competitors. Aggressive promotional strategies, digital ecosystem integration, and network effects are the main factors strengthening this dominant position. The market structure has shifted from a relatively competitive market to a concentrated oligopoly with a single dominant company. This situation has positive impacts in the form of easier market access and increased transactions for MSMEs, but also has the potential to create dependency and the risk of reduced competition in the long term. Therefore, regulatory oversight is needed to maintain the balance and sustainability of business competition in the Indonesian e-commerce industry.